The Effect of The Perception of Unnes Public Health Study Program Students on Early Detection of Breast Cancer Using Bse (Breast-Self Examination) - Fadhila, Efina Daitia; Kuswardinah, Asih; Sri Ratna Rahayu, Rr. (Public Health Perspective Journal, 2018)
Breast cancer is the leading cause of death of women in the world as well as in Indonesia. Nearly 70% of patients come to the hospital in an advanced stage, so it causes death. The most effective prevention strategy is early detection. BSE is a way of early detection with breast examination by self to detect any abnormalities that exist in the breast. Health action plans are grown with individual beliefs and perceptions of the diseases described through Health Belief Models. This study aims to analyze the effect of the perception of UNNES Public Health Study Program students on early detection of breast cancer using BSE.The study design used analytic with cross sectional approach through survey method. The population was all of undergraduate students of Public Health Program UNNES of fifth and seventh semester in 2017/2018. The samples were 74 respondents with the sampling technique used purposive sampling was continued quota sampling. Chi square test results show that there is significant an effect of perceived susceptibility on early detection of breast cancer using BSE (0,007); there is significant an effect of perceived severity on early detection of breast cancer using BSE (0,009); there is significant an effect of perceived benefits on early detection of breast cancer using BSE (0,003); and there is significant an effect of perceived barrier on early detection of breast cancer using BSE (0,000). Logistic regression test results show that perceived susceptibility has p-value 0,036 and OR 4.002; perceived severity has p-value 0,018 and OR 4.744; perceived benefits has p-value 0,004 and OR 7.247; and perceived barrier has p-value 0,048 and OR 3.435; concluded that the perception of benefit is the most influential variable to the the early detection of breast cancer using BSE. This study provides benefits as a thought contribution to the development of science in the field of reproductive health, disease concept, and behavioral science related to its application in early detection of breast cancer using BSE.